Current State of Community Pharmacist-Physician Collaboration - A Cross-sectional Survey Among Pharmacists in Poland - Iwona Wrześniewska - Wal; Jarosław Pinkas; Mateusz Jankowski (Polskie Towarzystwo Farmaceutyczne, 2024)
A patient-centered partnership between different healthcare professionals is critical to improving the quality of health services. While the cooperation of physicians, nurses, midwives, and paramedics is well documented, more and more attention is paid to the role of pharmacists in interdisciplinary care. This study aimed to evaluate the pharmacist's perception of the current state of community pharmacist-physician collaborative working as well as to identify barriers to the implementation of the community pharmacist-physician collaborative working model in Poland. This cross-sectional survey was carried out between October and December 2022 among community pharmacists in Poland. A total number of 1327 pharmacists from one of the largest franchise chain pharmacy networks in Poland were invited to take part in this study. The study questionnaire included 23 questions on the current state of pharmacist-physician collaborative working, the scope of cooperation, barriers to cooperation, and educational and organizational needs. Completed questionnaires were received from 635 pharmacists (response rate of 47.9%). Formal correction of the prescription (91.3%) was the most common cause of pharmacist-physician collaborative working. Moreover, 62.7% of pharmacists indicated that modification of ordered drugs was the reason for pharmacist-physician collaborative working. Only 3.3% of community pharmacists indicated that they collaborate with physicians during the drug review. Lack of IT systems enabling pharmacist-physician collaborative working (67.6%) and lack of recommendations on pharmacist-physician collaborative working (57.3%) were the most common barriers to collaboration with the physician. Pharmacists declare their readiness to cooperate with physicians, but there is a need to strengthen trust between both groups.